Educational Interface of Load Flow Methods Using Matlab Graphic User’s Interface Software (The International Journal of Engineering & Information Technology (IJEIT), 2024)
this paper introduces a new created programapplication built based on MATLAB programing languageto solve power system networks at steady state problems,which include power flow studies with significant approach.The load flow solution uses iterative techniques that arenamely, Newton-Raphson, Gauss-Seidel and Fast Decouple.After obtaining their results, line changes like lineswitching, tap changer and bus changing such as busdeletion or any specific information at the same bus can beeasily achieved. Moreover, the users can enter their ownsystem, and save it to apply the pervious analysis. Thisfriendly interactive program designed to be simple for theusers with accurate results and it can be applied for anynetwork.